Pelacak Matahari Dua Sumbu Menggunakan LDR untuk Meningkatkan Absorbsi Matahari - Parikesit, Elang; Purwadianto, Doddy; Sambada, FA. Rusdi (Media Teknika, 2017)
The position of the sun in the sky  always  changes  periodically.  A  lot of research has been doneto follow the sun's motion using a solar tracking system to increase the amount of solar energy that can be absorbed. The solar tracking system can be grouped into passive and active system. Active sun tracker system uses motor drive in following the motion of the sun. The current active tracking system is using one or two rotary axis. Active two-axis solar tracking system provides greater efficiency and effectiveness than one-axis solar tracking system. This study aims to increase the absorbable sun energy with a simpletwo-axis solar tracking system. This research has been  done by experimental method by making a model of two-axis sun tracker and  its field  data retrieval. The main parts of the model in this study are (1) LDR sensor, (2) microcontroller and  (3) motor drive.  Initial data of field test results shows  a maximum increase (269%) in absorbable solar energy on a model using a sun tracker than models that d o not use a solar tracking systemKeywords: tracker, sun, two-axis rotate, simple